2005
DOI: 10.1111/j.1526-4637.2005.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized Multicenter Trial Comparing Duloxetine with Placebo in the Management of Diabetic Peripheral Neuropathic Pain

Abstract: In this clinical trial, duloxetine 60 mg QD and duloxetine 60 mg BID were effective and safe in the management of DPNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
332
2
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 468 publications
(365 citation statements)
references
References 26 publications
19
332
2
12
Order By: Relevance
“…Duloxetine is a selective serotonin (5-HT) and norepinephrine (NE) reuptake inhibitor [40]. Duloxetine has been reported to be effective in diabetic neuropathic pain and recently in chronic orofacial pain disorders, such as burning mouth syndrome [41,42], suggesting other mechanisms of action. Indeed, duloxetine has been shown to act on certain sodium channels, blocking persistent late Nav1.7 currents.…”
Section: Discussionmentioning
confidence: 99%
“…Duloxetine is a selective serotonin (5-HT) and norepinephrine (NE) reuptake inhibitor [40]. Duloxetine has been reported to be effective in diabetic neuropathic pain and recently in chronic orofacial pain disorders, such as burning mouth syndrome [41,42], suggesting other mechanisms of action. Indeed, duloxetine has been shown to act on certain sodium channels, blocking persistent late Nav1.7 currents.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] In these studies, duloxetine 60 mg QD and 60 mg BID demonstrated significant improvement compared to placebo on the 24-hour average pain severity score. In addition, patients who completed one of the 12-week acute therapy phase studies were rerandomized to duloxetine 60 mg BID or routine care for 52 weeks of open-label treatment in order to evaluate the safety of duloxetine over long-term administration.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed in Raskin et al, 29 patients were eligible for the study if they were 18 years or older, and presented with pain due to bilateral peripheral neuropathy caused by type 1 or type 2 diabetes mellitus. The pain had to begin in the feet and with relatively symmetrical onset.…”
Section: Entry Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The literature regarding SNRI use for the prevention of chronic post-surgical pain is limited; however, given that the SNRI medication (duloxetine) is a firstline medication for the treatment of chronic neuropathic pain [67], its role in the prevention of chronic post-surgical pain should be further investigated. Duloxetine has been shown to be efficacious for the treatment of diabetic peripheral neuropathy and fibromyalgia [68][69][70][71]. Appropriately powered trials are necessary to examine the efficacy of the SNRIs in CPSP prevention, including dose-response studies and head-to-head comparisons with other drugs, such as pregabalin.…”
Section: Selective Norepinephrine and Serotonin Re-uptake Inhibitors mentioning
confidence: 99%